Parasitological and microbiological evaluation of sand from beaches in São Luís, Maranhão, Brazil - Viana, Alcileny Lima; Mesquita, Allana Dutra de; Serra, Anne Karoline Mendes; Bastos, Diana Karla Lourenço; Silva, Darlan Ferreira da; Silva, Maria Raimunda Chagas; Firmo, Wellyson da Cunha Araújo (O Mundo da Saúde, 2023)
Brazil has a coastline with large cities and a great flow of human activities, which can lead to contamination by microorganisms and parasites. Given this context, the objective of this study was to evaluate the parasitic and microbiological events in the sand of beaches in São Luís, Maranhão. Therefore, four samples were collected from three beaches, thus totaling 12 samples. Each area was divided into four distinct segments, two dry and two wet, and for each sample, sterile collectors were inserted into the sand at a depth of 20 centimeters. The samples were identified, placed in a Styrofoam box, and taken to the laboratory for analysis. The parasitological analysis was performed through spontaneous sedimentation and centrifugation, while the microbiological analysis used the COLItest® kit to determine total and thermotolerant coliforms (Escherichia coli). All the sand samples were positive (100%) for helminths and/or protozoa, and the most frequent helminth and protozoan were Trichuris trichiura (100%; n=12 ) and Giardia lamblia (83.3%; n=10), respectively. Microbiological analyses showed that 66.6% (8/12) were contaminated by total coliforms and 58.3% (7/12) by Escherichia coli. Collection point 3 of dry sand from São Marcos beach (Sm3S) showed the highest contamination by Escherichia coli (4.33x102 CFU/mL). The beaches on the seafront called Litorânea in São Luís are contaminated by parasites and fecal bacteria from animals or human sources on the beach. Thus, the probability of acquiring infections increases among individuals visiting these environments.